Relaxant Effect of Sodium Tanshinone IIA Sulphonate on Mouse Tracheal Smooth Muscle - Zhang, Yi-Lin; Xu, Jia-Wen; Wu, Xiong-Hao; Chen, Peng-Xiao; Wei, Fang; Gao, Dong-Dong; Chen, Xiao-Wen; Luo, Yu-Li; Zhu, Yun-Xin; Huang, Jiehong; Tan, Ya-Xia; Zhao, Lei; Zhou, Wen-Liang (Planta Medica, 2017)
Sodium tanshinone IIA sulphonate, a water-soluble derivative of tanshinone IIA, has been proven to possess versatile biological properties, but its pharmacological effect on tracheal smooth muscle remains elusive. This paper presents a study on the relaxant effect and underlying mechanisms of sodium tanshinone IIA sulphonate on mouse tracheal smooth muscle. The relaxant effect of sodium tanshinone IIA sulphonate was evaluated in mouse tracheal rings using a mechanical recording system. Intracellular Ca2+ concentration was measured in primary cultured tracheal smooth muscle cells using confocal imaging system. The results showed that sodium tanshinone IIA sulphonate induced dose-dependent relaxation of mouse tracheal rings in a β-adrenoceptor- and epithelium-independent manner. Pretreatment with the ATP-sensitive K+ channel blocker glibenclamide partly attenuated the relaxation response. Administration of sodium tanshinone IIA sulphonate notably inhibited the extracellular Ca2+-induced contraction. High KCl or carbachol-evoked elevation in the intracellular Ca2+ concentration was also abrogated by sodium tanshinone IIA sulphonate in tracheal smooth muscle cells. In conclusion, the tracheal relaxant effect of sodium tanshinone IIA sulphonate was independent of β-adrenoceptor and airway epithelium, mediated primarily by inhibition of extracellular Ca2+ influx via L-type voltage-dependent Ca2+ channels and partially by activation of the ATP-sensitive K+ channel. These results indicate the potential therapeutic value of sodium tanshinone IIA sulphonate for asthma treatment.
Keywords: Salvia miltiorrhiza; Lamiaceae; sodium tanshinone IIA sulphonate; relaxant effect; tracheal smooth muscle; Ca2+ channels